(untitled) - Kornhauser, David Henry (London, 1982)
This book introduce the urban landscape, the agrian landscape, the city in Japanese history, changes in the urban landscape after 1868. Historical aspects of the commercial landscape. Landscapes of the commercial and industry, 1868 - 1945. Reconstruction and the growth of the contemporary industrial landscape.
Keywords: Địa lý con người,Human geography; Nhật Bản,Japan